Gastrointestinal tissue : oxidative stress and dietary antioxidants - Gracia-Sancho, Jordi; Salvado, M. Josepa (Academic Press, $c [2017], 2017)
Gastrointestinal Tissue: Oxidative Stress and Dietary Antioxidants brings together leading experts from world renowned institutions, combining the basic mechanisms of gastrointestinal diseases with information regarding new and alternative treatments. The processes within the science of oxidative stress are described in concert with other processes, including apoptosis, cell signaling and receptor mediated responses, further recognizing that diseases are often multifactorial with oxidative stress as a component. By combining the critical molecular processes underlying free radical mediated pathologies and the role of dietary antioxidant molecules, a connection is made that helps advance therapies and the prevention of gastrointestinal pathological processes. This important reference is well designed with two complementary sections. Section One, Oxidative Stress and Gastroenterology, covers the basic processes of oxidative stress from molecular biology to whole organs, the gastrointestinal anatomy and sources of oxidative stress and free radicals and their products in gastrointestinal diseases. Section Two, Antioxidants and Gastroenterology covers antioxidants in foods, including plants and components.